Employee Engagement and Turnover Intention in Nepalese Banking Sector - Ghimire, Santosh Kumar (Perspectives on Higher Education, 2024)
The primary objective of this study is to examine the impact of employee engagement initiatives on turnover intention and to identify the key drivers of employee engagement. A sample of 200 employees from various commercial banks participated in this research. The methodology involved quantitative analysis, including correlation analysis and multiple regression analysis. The findings revealed significant negative correlations between employee engagement and turnover intention, indicating that as employee engagement increases, turnover intention tends to decrease. The study also identified four crucial factors that influence engagement: a supportive work environment, rewards and recognition programs, positive relationships with management, and clear career progression opportunities. The implications of this study suggest that organizations in the banking sector can mitigate turnover intention by strategically enhancing employee engagement through targeted initiatives and by fostering a work culture that prioritizes these key drivers of engagement.